2017
DOI: 10.3389/fphys.2017.00559
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive Transcranial Magnetic Stimulation Ameliorates Cognitive Impairment by Enhancing Neurogenesis and Suppressing Apoptosis in the Hippocampus in Rats with Ischemic Stroke

Abstract: Cognitive impairment is a serious mental deficit caused by stroke that can severely affect the quality of a survivor's life. Repetitive transcranial magnetic stimulation (rTMS) is a well-known rehabilitation modality that has been reported to exert neuroprotective effects after cerebral ischemic injury. In the present study, we evaluated the therapeutic efficacy of rTMS against post-stroke cognitive impairment (PSCI) and investigated the mechanisms underlying its effects in a middle cerebral artery occlusion (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
68
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 87 publications
(72 citation statements)
references
References 49 publications
2
68
0
2
Order By: Relevance
“…Similarly, studies of rTMS in cognitive impairment and dyskinesia after stroke have shown that rTMS has an effect on the BDNF-TrkB receptor pathway in the brain (Guo et al, 2017;Luo et al, 2017).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Similarly, studies of rTMS in cognitive impairment and dyskinesia after stroke have shown that rTMS has an effect on the BDNF-TrkB receptor pathway in the brain (Guo et al, 2017;Luo et al, 2017).…”
Section: Discussionmentioning
confidence: 96%
“…On one hand, studies on the effects of rTMS on depression and autism have shown that specific sites and frequencies of rTMS promote the release of endogenous GABA as well as reduce the loss of GABA A R on the postsynaptic membrane, thereby increasing the efficacy of GABAergic neurons (Dubin et al, ; Tan et al, ). Similarly, studies of rTMS in cognitive impairment and dyskinesia after stroke have shown that rTMS has an effect on the BDNF‐TrkB receptor pathway in the brain (Guo et al, ; Luo et al, ). On the other hand, neuroimaging and TMS measure showed cortical hyperactivity in the several types of sleep orders (Lanza, Cantone, et al, ; Lin et al, ; Nardone et al, ; Salas et al, ).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…However its therapeutic mechanisms are not completely clear. Previous studies have used rodent animals to investigate its potential cellular and molecular mechanisms related to synaptic plasticity (Guo, Lou, Han, Deng, & Huang, ; Ji et al, ; Tang, Thickbroom, & Rodger, ). Unlike humans, it is not practical to keep animals (including mouse or rat) stationary during the delivery of longer rTMS period.…”
Section: Introductionmentioning
confidence: 99%
“…In previous literature, investigators used the anesthesiology method (Sasso et al, ; Sykes et al, ), or by hand (Hesselberg, Wegener, & Buchholtz, ; Lim, Lee, Yoo, & Kwon, ; Sasso et al, ), or cloth, bag and straps (Ljubisavljevic et al, ); Tang et al, ), or some undefined devices (Guo et al, ). In animals, rTMS is often used 1–2 times each day (for minutes to tens of minutes each time), lasts for a few of days or tens of days (Fleischmann & Hirschmann, ; Guo et al, ; Ji et al, ). Thus, daily anesthesia may have potentially adverse effects in animals; Restraint by hand or by cloth, bag and tape may be laborious, or be potentially inconvenient for the delivery of rTMS, especially for a longer stimulation time (over 10 min).…”
Section: Introductionmentioning
confidence: 99%